Laryngeal complications by orotracheal intubation: Literature review - Mota, Luiz Alberto Alves; de Cavalho, Glauber Barbosa; Brito, Valeska Almeida (International Archives of Otorhinolaryngology, 2012)
Introduction: The injuries caused for the orotracheal intubation are common in our way and widely told by literature. Generally the pipe rank of or consequence of its permanence in the aerial ways of the patient is caused by accidents in. It has diverse types of larynx injuries, caused for multiple mechanisms.Objective: To verify, in literature, the main causes of laryngeal complications after- orotracheal intubation and its mechanisms of injury.Revision of Literature: The searched databases had been LILACS, BIREME and SCIELO. Were updated, books and theses had been used, delimiting itself the period enters 1953 the 2009. The keywords used for the search of articles had been: complications, injuries, larynx, intubation, endotracheal, orotracheal, granulomas, stenosis. 59 references had been selected. The used criteria of inclusion for the choice of articles had been the ones that had shown to the diverse types of injuries caused for the orotracheal intubation and its pathophysiology.Final Considerations: This revision of literature was motivated by the comment in the practical clinic of a great number of laryngeal sequels in patients submitted to the orotracheal intubation. Of that is ahead important the knowledge, for the professionals of the area of health, the types of complications and its causes, with intention to prevent them, adopting measured of prevention of these injuries.
Keywords: larynx; dysphonia; voice